Critique of rationality : judgement and creativity from Benjamin to Merleau-Ponty - O'Brien, John E. (Studies in critical social sciences, 2016)
In his 'Critique of Rationality', John Eustice O'Brien proposes a fascinating rectification for the distortion of technical necessity in Western Society due to unbridled instrumental reason. He begins with a review of this issue first raised by the Early German Romantics as discussed by Isaiah Berlin and Walter Benjamin. Following French social philosopher Maurice Merleau-Ponty's radically different apperceptive epistemology, he explores the possibility of a social world in which each is anchored by a preobjective disposition to meaning based on the intersubjective presence of all. This justifies the postulate of aesthetic-consciousness as the site of socialization in communities of meaning, as a frame for judgment and creativity. The struggle must continue for awakening that consciousness if an open society is to be realized.